2014
DOI: 10.1094/pdis-05-13-0491-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Colletotrichum truncatum Causing Anthracnose of Tomato in China

Abstract: growth was observed from surface sterilized tissues. Fungi were isolated, purified by single spore separation process, and subcultured to potato dextrose agar (PDA) plates. Growing on PDA, the surface of the colony was circular, fluffy, and shiny velvety-black, whereas the under surface was dark Prussian blue. Conidiophores were single or fascicled, brown to dark brown, rarely branched, multiseptate, and straight or often geniculate near the apex. Conidia were brown, smooth, fusiform, geniculate or hookshaped,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Morphological characters of these isolates were consistent and showed very distinctive curved conidia typical of the species. Colletotrichum truncatum has been reported as a pathogen of chili in several countries and an important pathogenic species that infects other plant crops causing serious damage (Sharma et al, 2005;Than et al, 2008;Mongkolporn & Taylor, 2011;Diao et al, 2014). Microsatellite-based marker analysis of C. truncatum populations from chili-growing regions in Southeast Asia revealed a high allele flow within and between populations, showing a high adaptive capacity of this pathogen to overcome host resistance (Ranathunge et al, 2009(Ranathunge et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological characters of these isolates were consistent and showed very distinctive curved conidia typical of the species. Colletotrichum truncatum has been reported as a pathogen of chili in several countries and an important pathogenic species that infects other plant crops causing serious damage (Sharma et al, 2005;Than et al, 2008;Mongkolporn & Taylor, 2011;Diao et al, 2014). Microsatellite-based marker analysis of C. truncatum populations from chili-growing regions in Southeast Asia revealed a high allele flow within and between populations, showing a high adaptive capacity of this pathogen to overcome host resistance (Ranathunge et al, 2009(Ranathunge et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…; Diao et al. ). In addition, C. truncatum can also cause mycotic keratitis and endophthalmitis in humans (Shivaprakash et al.…”
Section: Introductionmentioning
confidence: 97%
“…C. capsici) ). Aside from infecting peppers, C. truncatum has been reported to infect more than 460 plant species (http://nt.ars-grin.gov/fungaldatabases/) (Sutton et al 1992;Shenoy et al 2007;Damm et al 2009;Yang et al 2009;Wikee et al 2011;Huang et al 2013;Diao et al 2014). In addition, C. truncatum can also cause mycotic keratitis and endophthalmitis in humans (Shivaprakash et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…truncatum as a causal agent of chilli anthracnose has been reported in India (Chethana et al 2015) and is reported to cause tomato anthracnose in China (Diao et al 2014). To our knowledge, this is the first report of tomato anthracnose caused by C. truncatum in India.…”
mentioning
confidence: 98%